Carbohydrate Mouth Rinsing in Recreational Athletes: A Narrative Review of Performance Effects, Mechanisms, and Gastrointestinal Implications - Korohod, Tamara; Pietrzak-Chmiel, Martyna; Ramaneckaite, Paulina; Binkiewicz, Agnieszka; Ślesik, Maciej; Tadulewicz, Ilona; Łatkowska, Sylwia; Pawlik, Aleksandra; Pudzianowska, Aleksandra (Quality in Sport, 2026)
Background: Carbohydrate mouth rinsing (CMR) offers potential for athletes seeking performance benefits while minimizing gastrointestinal issues. Unlike the usual method of carbohydrate consumption, CMR allows athletes to swish carbohydrate solutions in their mouths without swallowing, which may trigger central mechanisms that enhance performance while avoiding GI problems. Aim: To review the current evidence regarding carbohydrate mouth rinsing effects on athletic performance and GI safety in recreational athletes. Material and Methods: A narrative review of peer-reviewed literature from examining CMR effects on exercise performance, cognitive function, and gastrointestinal outcomes. Data synthesis focused on the mechanism of action, performance outcomes, and practical applications for recreational athletes. Results: Meta-analytical evidence demonstrates modest ergogenic effects of CMR across exercise modalities. Optimal protocols utilize 6-6.5% maltodextrin solutions rinsed for ≤10 seconds. CMR effectiveness is enhanced under fed conditions during aerobic exercise. CMR reduces exercise-induced gastrointestinal symptoms while enhancing high-intensity muscular endurance. Preliminary evidence suggests cognitive performance benefits when combined with caffeine, though certainty remains low. Conclusions: Carbohydrate mouth rinsing is a simple yet effective ergogenic aid for recreational athletes, and it can be easily integrated into their routines. Using CMR before and during moderate-to-high-intensity workouts can enhance exercise capacity and performance while avoiding the gastrointestinal issues that often accompany carbohydrate intake. Since CMR offers a performance boost without the discomfort of GI distress, it stands out as a practical nutritional strategy for athletes. Moving forward, research should examine how men and women respond to CMR, how regular use may lead to chronic adaptations, and how best to tailor CMR strategies for different athletic groups.